CBS and MAT2A improve methionine‐mediated DNA synthesis through SAMTOR/mTORC1/S6K1/CAD pathway during embryo implantation. (12th November 2020) - Cai, Shuang; Ye, Qianhong; Zeng, Xiangzhou; Yang, Guangxin; Ye, Changchuan; Chen, Meixia; Yu, Haitao; Wang, Yuming; Wang, Gang; Huang, Shuo; Quan, Shuang; Zeng, Xiangfang; et al.
Abstract: Objectives: Early pregnancy loss is a major clinical concern in animal and human reproduction, which is largely influenced by embryo implantation. The importance of methionine for embryo implantation is widely neglected. Materials and methods: We performed a series of experiments with primiparous rats fed diets containing different levels of methionine during early pregnancy to investigate the role of methionine in embryonic implantation and pregnancy outcomes, and used them to perform in vivo metabolic assessments and in vitro uterine explant culture. In addition, through transcriptome analysis and silencing the expression of cystathionine β‐synthase (CBS, the key enzyme in transsulfuration pathway) and cell adhesion assay, we measured signalling within Ishikawa, pTr and JAR cells. Results: We determined the relevance and underlying mechanism of methionine on embryo implantation. We showed that methionine deprivation sharply decreased embryo implantation sites, expression of CBS and transsulfuration pathway end products, which were reversed by maternal methionine supplementation during early pregnancy. Moreover, we found CBS improved methionine‐mediated cell proliferation and DNA synthesis by CBS inhibition or interference. In addition, transcriptome analysis also revealed that CBS influenced the signalling pathway‐associated cell proliferation and DNA synthesis, as well as a correlation between CBS and methionine adenosyltransferase 2A (MAT2A), implying that MAT2A was possibly involved in cell proliferation and DNA synthesis. Further analysis revealed that MAT2A influenced S‐adenosylmethionine receptor SAMTOR expression, and SAMTOR activated mTORC1 and its downstream S6K1 and CAD, ultimately enhancing DNA synthesis in the embryo and uterus. Conclusions: Taken together, these studies demonstrate that CBS and MAT2A improve methionine‐mediated DNA synthesis through SAMTOR/mTORC1/S6K1/CAD pathway during embryo implantation. Abstract : Methionine deprivation sharply decreased embryo implantation sites, which were reversed by maternal methionine supplementation during early pregnancy. Methionine improved embryo proliferation and implantation through activating SAMTOR/mTORC1/S6K1/CAD signalling pathway.